Fagin's Coin of Truth: Economic Belief and Representation in Oliver Twist. (November 2014) - Clavin, Keith
<x xml:space="preserve">Abstract</x> This essay examines Fagin from Oliver Twist as a villain whose construction joins Victorian anxieties about counterfeiting and economic deceptiveness with separate yet related concerns about the author's role in representing criminal life. Dickens triangulates Fagin's identity through cultural fears about Jewish participation within secondary markets, increased distance between purchaser and seller in an expanding credit economy, and moral ambiguities in respect to fiction-making. Read against non-literary Victorian writing about counterfeiters and crime, Fagin can be understood as a forger of identities and narratives. His ability to exploit interpersonal belief and economic value is a central feature of his villainy and one with precedent in other aspects of Victorian financial life. Dickens critiques capitalist culture by associating it with the imitative, fictional, and Jewish culture. In contrast, he aligns sincerity and truth with the middle-class, normative characters. Throughout, he marks the distinction between these two groups with comic incidence. The marginalised figures are fodder for humour and irony, while the conventional heroes are earnest.